The Liquidity Trap - Grandmont, Jean-Michel; Laroque, Guy (Econometrica, 1976)
If the liquidity trap is viewed as a property of the aggregate demand for money (or liquid assets), it can be generated from the agents' microeconomic behavior only in special cases, even in the presence of the Keynesian assumption of inelastic expectations. On the other hand, in an economy where a central bank intervenes by open market operations, short run equilibrium interest rates on long term bonds tending to zero are associated with short run equilibrium money stocks which tend to infinity, once the Keynesian assumption of inelastic expectations is made.